(untitled) (Physical Culture and Sport: Scientific Perspective, 2022)
Amputation of the lower limb leads to the loss of its functions and, of course, entails significant changes in human life. However, in our time, technological advances allow people who have undergone amputation to live a full life and maintain social status. To achieve this goal, it is necessary to properly form an amputation stump, which will ensure long-term operation of the functional prosthesis. Competent, professionally trained rehabilitologists will correctly plan for each patient an individual rehabilitation program to care of the stump with a postoperative scar and under the future prosthesis; with their own participation and useful advice will strengthen the residual muscles, joint mobility, adaptation of the nervous system and the patiens body to limb loss. But first of all, it will protect the patient from contractures of the main joints of the lower limb, for the full functioning of the future prosthesis.